The Effects Of Early Menarche On Sexual And Reproductive Health: A Scoping Review - Hanny Wulandari; Dwi Ernawati; Sri Lestari (International Journal of Health Science and Technology, 2021)
Early menarche in adolescent girls has an effect on how quickly they come into contact with sexual life. This may have an impact on the increased incidence of unintended pregnancy, increased childbirth and abortion in adolescents. The condition of adolescents who are too young at menarche and poor reproductive health status will create problems with their menstruation, especially when the right sources of reproductive health information are not fully utilized. The aim of this scoping review is to interpret the effects of early menarche on sexual and reproductive health. The Scoping Review method was carried out using the following steps; 1) identifying research questions; 2) identifying relevant studies, through the Pubmed, Ebsco, and Wiley databases. In the search for articles, the keywords used are Effect OR Outcomes AND Menarche OR Menstruation OR Menstrua * OR menses OR "Early Menarche" AND "Reproductive Health" OR sexual reproduction * AND sexual behavior * OR "sexual debut" OR "Sexual Partners OR" unsafe sex "OR" unprotected sex ". The article criteria used are articles published from 2009 to 2019 and discussing the effects of early menarche on sexual and reproductive health; 3) the selection of articles was described using the Prisma Flow Chart where in full text search results, 18 articles were obtained and 9 articles was used for the review as these have quality assessment and according to population, methods, and results; 4) carrying out data charting; and 5) carrying out the compilation of results reports. The nine articles used as review materials discussed sexual health and early sexual reproduction in 101 respondents (21%) among sexually active students, 15 out of 89 students (16.9%) had low use of contraception, diseases of sexual health and reproduction (herpes simplex type-2, that is, women aged 14 who have experienced menarche have had sexual intercourse, HIV, which is 5.6% positive, as well as factors that affect sexual and reproductive health (45% education, 81.4% knowledge, economy due to low income, 60% sexual desire at the age of 14 years and only 11% who have not been sexually active at the age of 17 years). Early menarche and high sexual desire are health problems that have serious implications for adolescents. Provision of appropriate information and education on sexual and reproductive health for adolescents is urgently needed. It is hoped that the findings from the articles that have been reviewed can contribute to the importance of providing sex education from an early age.